Історико-правові аспекти конституційних основ правового статусу суддів у міжвоєнний період(1921-1939 рр.) на теренах радянської України - Кравчук, В.; Kravchuk, V. (Східноєвропейський національний університет імені Лесі Українки, 2017)
Стаття присвячена аналізу конституційно-правових основ статусу суддів у міжвоєнний період (1921-1939 рр.) на теренах радянської України. Визначено фактори, що впливали на їх формування. Досліджено динаміку окремих елементів правового статусу суддів в ході розробки проектів конституційних актів. Зроблено висновок про те, що нормативні положення, що закріплювали правовий статус суддів, формально маскувалися в перших українських радянських конституціях, а принцип незалежності суддів не мав жодного практичного наповнення, оскільки процедура виборів була номінальною. The article provides historical analysis of the genesis of the judges’ legal statusin the interwar period (1921-1939) in the Soviet Ukraine. The emphasis is laid on the establishment and evolution of the institute of judges’ legal status, although it plays a different role and has different political and legal status depending on the type of government. The author assumes that during this period some elements of the legal status of judges had been established, including requirements to the position of a judge, the procedure of the judges appointment, oath of ajudge, powers of judges, responsibility of judges, guarantees of the judges’ safety/security. Soviet interwarperiod, when the constitutional foundations of the legal status of judges in Ukraine were established, is characterized by certain inner evolution. Notwithstanding, that these historical stage was marked by the formation and strengthening of the repressive totalitarian regime, the norms that regulated the legal status of judges had been formally hidden in the first Ukrainian Soviet constitutions, the principle of judicial independence had no practical content, since the judges election procedure was nominal.
Historical and Legal Aspects of the Constitutional Foundations of the Judges’ Legal Status in the Interwar Period (1921-1939) in the Soviet Ukraine
Keywords: правовий статус; правовий статус судді; правосуддя; суддя; судова система; legal status; legal status of a judge; justice; judge; judicial system